Phenolic profile and antioxidative properties of the beefsteak fungus Fistulina hepatica - Silva, Branca M. (2006)
The phenolic composition of the edible beefsteak fungus Fistulina hepatica was determined by HPLC/DAD. The results showed a profile composed by caffeic, p-coumaric and ellagic acids, hyperoside and quercetin. Ellagic acid was the main compound in this species. Beefsteak fungus was also investigated for its capacity to act as a scavenger of DPPH radical and reactive oxygen species (superoxide radical, hydroxyl radical and hypochlorous acid). Good results were obtained against DPPH and superoxide radicals and hypochlorous acid but a prooxidant effect was observed for hydroxyl radical.